Systems Biology for Signaling Networks - Choi, Sangdun. (Systems Biology, 2010)
Systems biology is a new and exciting field that is an extension of many others including: Molecular Biology, Immunology, Genetics, Computational Biology, and Mathematical Biology. The goal is to understand the relationships from genes to organisms through networks in biological systems. The series Systems Biology examines an array of topics, in systems biology studies, ranging from molecular parts of cells to network modeling. The first volume in this series, Systems Biology of Signaling Networks, contains a collection of work in regulatory signaling networks and the use of large-scale omics data.